Standard requirements for clinical very high energy electron and ultra high dose rate medical devices - Pensavalle, J. H.; Di Martino, F.; Cavalieri, A.; Celentano, M.; De Gregorio, A.; Di Francesco, M.; Franciosini, G.; Galluzzo, L.; Masturzo, L.; Milluzzo, G.; Montay-Gruel, P.; Paiar, F.; et al. (Frontiers in Physics, 2024)
Very High-Energy Electrons (VHEE) present a promising innovation in radiation therapy (RT), particularly for the treatment of deep-seated tumors using Ultra High Dose Rate (UHDR) within the framework of FLASH-RT. VHEE offers significant advantages, such as improved tumor targeting, reduced treatment times, and potential utilization of the FLASH effect, which may minimize normal tissue toxicity. However, the lack of an international technical standard for VHEE systems, especially for UHDR applications, remains a critical challenge. Current standards for radiation therapy equipment, such as IEC 60601-2-1 and IEC 60601-2-64, do not encompass VHEE technology. This regulatory gap underscores the need for developing a structured international standard to ensure the basic safety and essential performance of VHEE medical devices. Addressing this challenge requires overcoming complex dose delivery issues, such as the interaction of multiple fields and beam conformality and incorporating novel techniques like broad beam or pencil beam scanning. Establishing comprehensive regulatory standards is essential to ensure patient safety, consistent treatment practices, and the successful clinical integration of VHEE systems. These standards must encompass design guidelines, radiation protection protocols, and integration with existing oncology practices. Collaborative research and development efforts are crucial to formulating evidence-based guidelines, fostering the safe and effective use of VHEE in clinical settings. By addressing these challenges, VHEE technology has the potential to revolutionize cancer therapy, particularly for deep-seated tumors, while enhancing therapeutic outcomes for patients.